Decree on Climate 2019. What resources support forests and silviculture in our cities? - Salbitano F; Sanesi G (Forest@, 2019)
The Decree on Climate 2019 focuses on reforestation campaigns and silviculture actions applied to existing forests of Italian metropolitan cities, incurring a total expenditure of €30 million in the next two years. By supporting urban and peri-urban forestry programmes, the decree represents an innovative scheme within the framework of environmental legislation on climate actions. The decision appears strategic as it depicts new scenarios for the cities of tomorrow involving sequence design, implementation and management of urban forests as key components to challenge climate change effects on the urban environment. Italian research in the field of urban forestry and related issues is well prepared to tackle the challenge thanks to 25 years of experience in “planting, growing, and caring for” ideas, knowledge, and methods applied to the ecology and functioning of urban and peri-urban forests. This wealth of experience is at the service of the community and of stakeholders who will be directly or indirectly involved in the implementation of the Decree on Climate 2019.